Plato’s Theory of Education and its Relevence to Sri Lanka’s Education System - Jamahir, P.M. (University of Jaffna, 2018)
This paper attempts to discuss the Plato’s theory of education and its relevance to Sri Lanka’s education system. Education means ‘upbringing’ and it deals with the cultivation of virtues. It gives humans the ability to achieve their fullest personal, spiritual, physical, mental, emotional and intellectual potentials. During the learning process, pupils acquire variety of skills, creativity, thinking knowledge and attitudes. The aim of education is formulated by educational thinkers and policy makers who emphasized that the aim of education is social justices, happiness and freedom. And the educational system should be work out reached this highest goal, in their perspective. Plato’s approach to education is a holistic, including facts, skill, physical discipline, ethics, music, and art as well. His great concerns was on generating more creative and talents pupils who can shine as a ruler of the state and to lead the government for benefits of the nation. The present education policies of most countries try best to promote educational setup to achieve in the same goals expressed by Plato in personal and public life of children and. Though there is a significant difference exists between the educational policy of Plato’s time and the present context, there is the assumption, that to some extent Plato’s educational philosophy and new educational paradigm are the same namely, the concept of physical education, moral education, aesthetic education, liberal education, music in education, educational guidance, free education for all, citizenship, community service, and discipline in schools. It shows that our present day curriculum is already formulated and emphasized in the Greeks and Plato’s thought. In this point, exploring the educational theory of Plato will expand our knowledge in the field of education, to create responsible citizens and to the development of the welfare of the society. The conceptual analysis and comparative method used in this study are mainly based on Plato’s two dialogues: The Republic and Laws. In addition, data is collected from books with critical analysis, scholarly articles, conventions, newspapers and recognized source of web.
Keywords: Education; Paradigm; Virtue; Ruler; Philosopher king